Standard versus widefield angiography in detecting new vessels in proliferative diabetic retinopathy - S Sindhu; Shruti Chandra; Mahesh Gopalakrishnan (Kerala Journal of Ophthalmology, 2017)
Purpose: The purpose of this study was to find out the accuracy of detecting new vessels (NVE) using standard field and widefield (SF and WF) angiographic imaging modality in eyes with proliferative diabetic retinopathy (PDR). Methods: This is a retrospective, cross-sectional study of 88 patients who underwent fundus fluorescein angiography (FFA) for suspected PDR from March 2015 to August 2015. Angiography was performed on the SPECTRALIS (Heidelberg, Germany) using SF 55° lens at primary, up, down, right, and left gaze and Staurenghi WF 102° lens in primary gaze. NVE were diagnosed by standard definition on FFA and a number of NVE were counted. Comparison of NVE detected on WF versus SF in primary gaze and WF versus SF in peripheral gaze was made. Fisher's exact t-test was used for statistical analysis. Results: The mean age of the patients was 56.87 ± 12.42 years. PDR was bilateral in 73 eyes and unilateral in 15 eyes. On comparing WF versus SF in primary gaze, 117 and 99 eyes were correctly detected as having NVE, respectively. On comparison of WF with SF in peripheral gaze, NVE picked up was 117 and 114 eyes, respectively. The missed NVE count in both comparisons was found to be statistically significant (P < 0.02). The sensitivity of SF in primary gaze was calculated to be 84.6%, whereas in peripheral gazes, it improved to 97.4%. Conclusion: As evident by our study results, SF images in primary as well as all peripheral gazes tend to miss out on NVE, thereby incorrectly diagnosing PDR eyes as non-PDR, which were picked up on WF as having NVE. Hence, we propose that WF angiography can be considered as gold standard for accurately diagnosing the presence of NVE in eyes with PDR.